2021
DOI: 10.3389/fphys.2021.744548
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation Improves Uterine Receptivity in a Rat Model of Vitamin D Deficiency: A Possible Role of HOXA-10/FKBP52 Axis

Abstract: Synchronized uterine receptivity with the time of implantation is crucial for pregnancy continuity. Vitamin D (VD) deficiency has been linked to the failure of implantation. Therefore, we tested the link between the Homeobox transcription factor-10/immunophilin FK506-binding protein 52 (HOXA-10/FKBP52) axis and the uterine receptivity in VD-deficient rats. The effect of VD supplementation at different doses was also investigated. Forty-eight pregnant rats were divided into six groups (eight/group); normal cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This effect is achieved by binding to its VDRs receptor on the endometrium, which in turn increases the expression of the HOXA10 gene, a crucial gene involved in both placentation and implantation [ 50 , 51 ]. In a rat model, supplementation of VD positively influenced the proper endometrial priming required for successful implantation and the continuation of pregnancy by enhancing progesterone and HOXA 10 expression [ 52 ]. Indeed, after VD administration, an increase in HOXA-10 was observed together with an improvement in endometrial decidualization in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is achieved by binding to its VDRs receptor on the endometrium, which in turn increases the expression of the HOXA10 gene, a crucial gene involved in both placentation and implantation [ 50 , 51 ]. In a rat model, supplementation of VD positively influenced the proper endometrial priming required for successful implantation and the continuation of pregnancy by enhancing progesterone and HOXA 10 expression [ 52 ]. Indeed, after VD administration, an increase in HOXA-10 was observed together with an improvement in endometrial decidualization in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the role of VD sufficiency during IVF procedures, one study detected higher pregnancy rate during IVF procedures in women showing higher endometrial VD receptor (VDR) expression levels, especially during the implantation window of the menstrual cycle than in women with decreased expression [23] . Another study found VD supplemental therapy (VDST) increased serum vitamin D3 levels with subsequent higher implantation rates during IVF [24] . Recently, a widepopulation study of women undergoing ICSI detected a positive correlation between basal serum levels of 25-OHVD and basal levels of follicle-stimulating hormone, estradiol, anti-Müllerian hormone, antral follicle count, and a number of the retrieved oocytes [19] .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, the values of 25(OH)D and endometrial thickness were significantly increased in the pregnancy group after intracytoplasmic sperm injection, suggesting that 25(OH)D deficiency in women could affect endometrial thickness [ 190 ]. Ashour et al [ 191 ] supplemented vitamin D to a rat model of vitamin D deficiency and found that vitamin D improved the endometrial receptivity of rats by adjusting the expression of HOXA-10. Additionally, a systematic review has investigated the relationship between vitamin D and the success rate of embryo transfer, and found that women with more adequate vitamin D showed higher clinical pregnancy rate and that higher vitamin D levels could improve the success rate of ART [ 192 ].…”
Section: Methodsmentioning
confidence: 99%